Spore special issue: Global warming: Doing business in a time of climate change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2015)
Smallholder farmers in developing countries are likely to be hardest hit by climate change due to agriculture’s vulnerability to extreme weather patterns and the low level of resilience of farming to climate variability and change. The good news is that innovative approaches are being developed to meet this challenge. One of these approaches, climatesmart agriculture (CSA), aims to increase farm productivity and incomes in a sustainable manner, enable farmers to adapt and build resilience to climate change and, where possible, reduce greenhouse gas emissions.